Rules of projecting freight terminal in airports of Ukraine - Першаков, В. М. (Proceedings of National Aviation University (archive), 2000)
Analyzed are the existing norms (text-book, procedures, recommendations) in proposed freight complexes of airports, which do not meet the modem international requirements and the market economy of Ukraine. Grounded on the made analysis developed were conclusion and propositions concerning new rules of projecting freight terminals of Ukrainian airports